Improved two-photon photopolymerisation and optical trapping with aberration-corrected structured light - Armstrong, D. J.; Stilgoe, A. B; Nieminen, T. A.; Rubinsztein-Dunlop, H. (Frontiers in Nanotechnology, 2022)
We demonstrate the effectiveness of phase only aberration corrections of structured light and their application to versatile optical trapping setups. We calculate phase corrections before (ex-situ) and after (in-situ) a high numerical aperture microscope objective using a spatial light modulator (SLM), and investigate how these corrections can be used to improve the efficiency and resolution of micro-structures fabricated through two-photon-photopolymerisation (2PP). We apply a phase retrieval algorithm to correct for distortions in a femto-second laser that enables the fabrication of 3D structures using as many as 50 simultaneous foci. The inclusion of aberration correction in the fabrication process shows improved confinement of optically trapped particles and more efficient polymerisation while minimising intensity variations at individual foci, which potentially damage the structure during fabrication. We show that phase corrections allow for consistent voxel sizes, increased sharpness, and an expanded effective printing range when using an SLM, while also allowing for closer proximity of individual trap foci, minimising interference effects that hinder fabrication resolution.